Regional Branding as an Effort to Promote a Sustainable Environment (Jurnal Bina Praja, 2023)
Regional branding is an essential strategic way for increasing the development or progress of a region. Many studies that discuss city branding are associated with the tourism sector or others to increase regional competitiveness. Meanwhile, it is no less important to carry out regional branding, such as green branding, which focuses on global warming issues, to minimize environmental damage. So, regional branding is an increasingly important position because only the government is currently playing a role in promoting regions to create a sustainable living environment. This study aims to analyze the effect of regional branding and other factors, such as fiscal, economic, and social decentralization factors, on improving environmental quality. This study uses panel regression impact: difference in difference to explain the impact before and after branding on environmental quality. The data used was secondary panel data from 34 provinces during 2016-2021. The results showed that urban branding increased the environmental quality index after the Climate Conference 25 (COP25). Meanwhile, fiscal decentralization will likely encourage an increase in the environmental quality index. The increase in urban population and electricity consumption will likely reduce the environmental quality index. In this case, the central government needs to invite local governments and other stakeholders to collaborate and work together to improve regional branding focusing on the environment and environmental mapping qualifications.